The Effect of Quranic Extracurricular Activities on the Academic Self-efficacy of Female High School Students in Khoy - Shahande 1*, Amene (Shahroud Journal of Medical Sciences, 2021)
Background: Quranic extracurricular activities, with the optimal use of the abilities of intelligence, contemplation, and concentration in the verses of the Qur'an, play an important role in all aspects of human life. This study aimed to investigate the effect of Qur'anic extracurricular activities on the academic self-efficacy of female high school students in Khoy city. Methods: This research was applied in terms of purpose and method, and was conducted cross-sectionally in 2018 in Khoy high schools. The statistical population of this study was all-female high school students in Khoy, of which 60 were selected as clusters and were divided into two groups of 30 available. Data were collected through an eight-item self-efficacy study questionnaire Motivated Strategies for Learning Questionnaire (MSLQ). Results: The distribution of the high percentage of students' academic self-efficacy by group shows that the Qur'anic extracurricular activities of 23.8% have a greater impact on the academic self-efficacy of female students. The study of intergroup effects also showed that the group factor had a significant effect on academic self-efficacy η2p=0.019, Pvalue=0.03, F(1,58)=4.820. Therefore, it can be said that group Qur'anic extracurricular activities have had a great impact on academic self-efficacy in female high school students in Khoy. Conclusions: Differences in the mean and standard deviation in students with Qur'anic extracurricular activities (Mean= 47.03, SD= 4.64) and students without Qur'anic extracurricular activities (Mean= 44.20, SD=5.32) with a value of (t= 2.196) and a degree of freedom (df= 58) at a significant level of 0.03 is significant. The use of Quranic activities to increase academic self-efficacy to make positive changes in students' attitudes promotes the level of culture and improves their performance. Therefore, trying to identify the necessary Qur'anic strategies to improve students' academic self-efficacy has an effective role in their educational, professional, and family future. Keywords: Quranic extracurricular activities, Academic self-efficacy, Students.